(untitled) (Journal of Management and Business Education, 2025)
Faced with the new challenges of the accounting profession and Higher education, generated by the interruption of Artificial Intelligence (AI), we propose to systematically integrate it, with an ethical vision, in our educational process. Therefore, with this work, which is included within a broader one, we intend to explore the use of AI by university students and their perception of their experience, the future impact, ethical aspects and potential risks, both in the higher education as well as in the profession related to Accounting and Finance, what they consider their level of training to be, as well as what their training needs are. We have used an exploratory quantitative methodological approach, using a survey with α= .922 (Cronbach’s Alpha) and a non-probabilistic sample of 145 students. The results reveal that they use AI little due to lack of knowledge and preferring traditional methods, concentrating their experience on the general search for information through ChatGPT, estimating a moderate future impact both at the educational and professional levels. Furthermore, it is evident that their training in use, ethics and risk prevention is limited, which shows the need to create training programs, providing greater ethical awareness.